Clarke and Braun’s Six-Step Thematic Analysis Process. - Maria A. Afadapa (22683548) (2025)
This figure illustrates the six phases of thematic analysis as outlined by Clarke and Braun: (1) Familiarization with the data, (2) Generating initial codes, (3) Combining codes to themes, (4) Reviewing themes, (5) Determining themes’ significance, and (6) Reporting findings.